THE INFLUENCE OF BEN OSAWE’S DRAUGHTMANSHIP ON HIS SCULPTURES - Egwali, Franklyn Chu (European Scientific Journal, ESJ, 2014)
Most often people consider Ben Osawe as a genius in three dimensional art renditions, this is a welcome development. But to only think so amounts to short sightedness as the cradle of authorial identity of an artist lies in the intricate lines of expression the way words determine the dexterity of a wordsmith. It is very important to uphold that Osawe’s drawings powerfully gave strength to his sculptures. In fact his drawings radically influenced and redefined his sculptures. They have left positive legacies behind for upcoming artists. This seminar paper therefore seeks to identify the identity of Osawe’s artforms through his draughtsmanship (drawings). In effect how his drawings positively transformed his sculptures from Camberwell School of art in London to the twilight of his practice is what this paper seeks to establish.